2019
DOI: 10.33549/physiolres.933958
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in intraluminal thread model of middle cerebral artery occlusion in rats

Abstract: Stroke is despite of progressive improvements in treatment and reperfusion strategies one of the most devastating human pathology. However, as quality of acute health care improves and more people survive ischemic attack, healthcare specialists have to solve new challenges to preserve reasonable quality of life to these patients. Thus, novel approaches which prevents comorbidities of stroke and improve quality of life of stroke survivors in general has to be developed and experimentally tested. The aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Fluorodeoxyglucose (18F-DG; ÚJV, Czech Republic) has been used in our experiments. Our team has expertise with 18F-DG use in small animals ( Svoboda et al, 2019 ). Animals were intravenously injected (jugular vein) with the selected dose of 18F-DG (10 – 15 MBq for PD12 and PD13 animals and 20–22 MBq for PD34 animals) dissolved in 0.2 or 0.4 (PD34) ml of saline, while shortly anaesthetized by isoflurane (ISF).…”
Section: Methodsmentioning
confidence: 99%
“…Fluorodeoxyglucose (18F-DG; ÚJV, Czech Republic) has been used in our experiments. Our team has expertise with 18F-DG use in small animals ( Svoboda et al, 2019 ). Animals were intravenously injected (jugular vein) with the selected dose of 18F-DG (10 – 15 MBq for PD12 and PD13 animals and 20–22 MBq for PD34 animals) dissolved in 0.2 or 0.4 (PD34) ml of saline, while shortly anaesthetized by isoflurane (ISF).…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to the fact that the structure of the middle cerebral artery in SD rats highly varies from one rat to another [ 21 , 32 ]. Nevertheless, previous studies on the FCI model using Long–Evans (LE) rats do not show any deviation or variability related to this rat strain [ 33 , 34 , 35 , 36 , 37 , 38 ]. We therefore chose to induce the ischemic stroke specifically in LE rats.…”
Section: Discussionmentioning
confidence: 80%
“…Several pre-clinical studies using mouse models of ischemic stroke have used [ 18 F]FDG/PET imaging as the primary technique to evaluate ischemic brain function and treatment efficacy. All research cited in this review on mouse models of ischemic stroke published between 2015 and 2022 found that the most commonly used mouse model was MCAO performed by intraluminal suturing [22,25,28,[30][31][32][33][37][38][39][40][41][42][43][44][45][46]. In the context of the goal of the research, variations of this technique are used, such as.…”
Section: [ 18 F]fdg/pet and Murine Models Of Ischemic Strokementioning
confidence: 99%